Clinical Significance of Lipoprotein and Ceruloplasmin Variation in Preeclampsia - Nnodim Johnkennedy; Katherine A. Emenikeh; Nwaokoro Joakin Chidozie (IOASD Journal of Medical and Pharmaceutical Sciences, 2026)
Preeclampsia is a multisystem illness of pregnancy characterised by new-onset hypertension after 20 weeks of gestation and end-organ failure of varied severity. Placental dysfunction, maternal endothelial injury, inflammation, oxidative stress, and aberrant lipid metabolism are identified as significant features of the disease process, however the detailed pathophysiology is still not fully understood. Preeclamptic women have shown changes in circulating lipoproteins, including an increase in triglycerides, total cholesterol, low-density lipoprotein cholesterol (LDL-C) and a decrease in high-density lipoprotein cholesterol (HDL-C). Ceruloplasmin is a copper-containing acute phase protein with key antioxidant and ferroxidase properties, which has also been shown to be increased in preeclamptic pregnancy. Meta-analysis of 15 trials and 1,927 women showed that serum ceruloplasmin concentrations were considerably higher in women with preeclampsia than in healthy pregnant controls. These biochemical abnormalities may reflect interplay between the dyslipidaemia, oxidative stress and endothelial dysfunction characteristic of preeclampsia. Thus, lipoprotein and ceruloplasmin assays may be beneficial to give us information on the metabolic and oxidative milieu accompanying the disease. But the evidence to date does not support their usage as a stand-alone diagnostic tool. Their greatest clinical utility may be in combination with established clinical indicators and other biochemical or placental biomarkers for risk stratification, illness monitoring and knowledge of pathogenesis